Evaluation of ground vibration resulting from a heavy vehicle passing over transverse rumble strips : a case study in Kluang Road FT050 - Mohd Shahmerulakmal M Zain; Mohd Hanifi Othman; Nasradeen. A. Khalifa; Mohd Bazli Mohd Fozi; Julaihie Sabri; Adi Hizami Mohammad Tamin; Aziman Madun (Penerbit Universiti Kebangsaan Malaysia, 2021)
The transverse rumble strip (TRS) is one of the methods used to improve the driver's alertness to its driving and reduce their speed. However, the presence of a TRS causes unevenness on the road surface and may result in ground vibration when heavy vehicles passes it. This ground vibration may cause discomfort to the people living adjacent to the road. Therefore, there is a need to evaluate the level of ground vibration resulting from heavy vehicles passing over TRS especially on typical federal road in Malaysia which contains high percentage of fast-moving heavy vehicles. Ground vibration assessment study was conducted at federal road of Kluang-Batu Pahat Road (FT050) by using existing heavy vehicles in the traffic stream as study samples. ICP accelerometer and computer software Dewesoft7 have been used to measure and analyse the level of vibration generated. The results indicate heavy vehicles at a speed of 50 km/h, 33 km/h and 24km/h generate ground vibration level of 1.24 mm/s, 2.30 mm/s and 0.76 mm/s respectively. Other factors such as the weight of the heavy vehicles may involve in ground vibration generation mechanism as the results shown that there was no direct correlation between vehicle speed and level of ground vibration. All the generated ground vibration levels were found to be within the allowable limit set by Department of Environment Malaysia (DOE) standard guidelines.